Dampak Penggunaan Augmented reality dalam Pembelajaran Biologi: Systematic Literature Review - Zahra, Fatimah Az; Suhendi, Suhendi (Universitas Muhammadiyah Magelang, 2026)
This study aims to map the impact of Augmented reality in biology learning and to identify factors influencing variations in research findings. The study employed a Systematic Literature Review (SLR) method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Research data were collected from Google Scholar and Scopus databases with a publication range from 2020 to 2025. The data collection process involved article identification, duplicate removal, title and abstract screening, and full-text review using the Covidence software. Data were analyzed using descriptive analysis and thematic synthesis of studies that met the inclusion criteria. The results show that among the 18 analyzed studies, 15 studies reported positive effects of Augmented reality on students’ conceptual understanding, while 3 studies showed limited effects. The findings also indicate that the effectiveness of Augmented reality is influenced by several factors, including three-dimensional visualization, students’ motivation and engagement, teachers’ roles, ease of technology use, and technological infrastructure support. Therefore, Augmented reality has strong potential as an innovative learning medium that can enhance conceptual understanding in biology learning.